Pelatihan Literasi Keuangan Syariah Melalui Metode Getok Tular (Word Of Mouth Communication) - Zaldy Suhatman; Sahlan Hasbi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2019)
Based on the national survey data of the Financial Services Authority, the conventional Financial literacy index in Indonesia reaches 29.1% while the Sharia financial literacy index is only 8.1% or lower than 30 percent conventional financial literacy. This condition shows the lack of public understanding of the product features and activities of sharia finance institutions considering that the terms used are generally a new term for Indonesian society. Since the year 2018 United Cooperative Relatives of Pulo Kambing converted into a Shariah cooperative. But from 33 managers and managers of active cooperatives, only 12.1% or only 4 people) who have participated in the training of sharia cooperatives. The solutions offered to solve the problem of knowledge gaps of managers, managers, and members of sharia cooperatives, the sharia financial literacy is done by Getok Tular (Word Of Mouth Communication) method which aims to Give birth to change agents who are ready to transmit his knowledge about sharia-urban. Based on the results of devotion, there is increased post-training knowledge. Based on the results of pretests and posttest there is a hike of 35 points so that it can be concluded that there is an increase in participants about the sharia cooperative and can be categorized that the trainees have fulfilled the criteria as an agent Infanteer tular (Word Of Mouth Communication strategy).